PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN IPAS DI KELAS V SDN 17 BATU GADANG KOTA PADANG: PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN IPAS DI KELAS V SDN 17 BATU GADANG KOTA PADANG - Qumairoh, Intan; Zuryanty; Amini, Risda; Media, Afriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of fifth-grade students in the Natural and Social Sciences (IPAS) subject at SDN 17 Batu Gadang, Padang City. These low outcomes were attributed to teacher-centered instruction, a lack of student engagement in the learning process, and the suboptimal use of learning models capable of fostering students' critical thinking abilities and skills. The study employed a mixed-methods approach (qualitative and quantitative) using Classroom Action Research (CAR) conducted over two cycles. Each cycle comprised planning, implementation, observation, and reflection stages. The research subjects were the teacher and 25 fifth-grade students at SDN 17 Batu Gadang, Padang City. Data were collected through observation, tests, and documentation, and subsequently analyzed using qualitative and quantitative methods. The average lesson plan (RPM) assessment score increased from 89.25% (good) to 96.40% (excellent). Teacher activity scores rose from 82.75 (good) to 93.75 (excellent), while student activity scores increased from 86.1% (good) to 96.80% (excellent). Furthermore, the students' average learning outcomes improved from 65.71 (fair) in Cycle I to 85.46 (good) in Cycle II. Thus, the Project-Based Learning model proved effective in enhancing IPAS learning outcomes in primary school.